Gangguan Kognitif Pasca-Stroke – Tinjauan Sistematik: Analisis - Pradhea, Tifani Antonia; Dwikarlina, Intan; Putra, Aulia Wiratama; Agustina, Lisa; Nardian, Derajat Fauzan (PT Kalbe Farma Tbk., 2024)
Introduction: The increasing number of stroke survivors was accompanied by an increase of cognitive impairment incidence as one of the post-stroke long-term consequences. Post-stroke cognitive impairment needs to be highlighted because of impact on reducing the quality of life, especially in the elderly. Methods: Literature was extensively searched across ScienceDirect, PubMed, Google Scholar, and Cochrane databases, using several predetermined keywords. Results and Discussion: Nine articles were analyzed. MMSE and MoCA assessments were used as parameters of post-stroke cognitive impairment. Most patients experience post-stroke cognitive impairment ranging from mild cognitive impairment to vascular dementia or other types of dementia. Risk factors include older age, female, lower and shorter education, location of lesions in the left hemisphere with involvement of certain brain structures, uncontrolled and fluctuating blood pressure, family history of stroke, comorbid diseases, as well as an individualistic social life. Conclusion: Stroke significantly increases the risk of cognitive impairment anddementia.